2014
DOI: 10.1038/bjc.2014.452
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E melanoma cells secrete factors that activate stromal fibroblasts and enhance tumourigenicity

Abstract: Background:Melanoma, the most lethal form of skin cancer, is responsible for over 80% of all skin cancer deaths and is highly metastatic, readily spreading to the lymph nodes or metastasising to other organs. The frequent genetic mutation found in metastatic melanoma, BRAFV600E, results in constitutive activation of the mitogen-activated protein kinase pathway.Methods:In this study, we utilised genetically engineered melanoma cell lines and xenograft mouse models to investigate how BRAFV600E affected cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 52 publications
7
47
0
Order By: Relevance
“…Our data support previous studies showing that in BRAF V600E melanoma cells, inhibition of either BRAF or MEK results in a decrease in the release of immunosuppressive soluble factors IL-6, IL-8, IL-10, and VEGF [18,22,25,26]. These cytokines inhibit the T-cell-stimulatory function of DCs and play various roles in tumor progression through modulation of the TME [12,25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data support previous studies showing that in BRAF V600E melanoma cells, inhibition of either BRAF or MEK results in a decrease in the release of immunosuppressive soluble factors IL-6, IL-8, IL-10, and VEGF [18,22,25,26]. These cytokines inhibit the T-cell-stimulatory function of DCs and play various roles in tumor progression through modulation of the TME [12,25].…”
Section: Discussionsupporting
confidence: 90%
“…PLX-4032 treatment did not result in a significant change in any of the protein levels. In addition, similar to what has been shown in the literature [22][23][24], several cell lines in the BRAF WT group showed a paradoxical increase in secreted proteins upon MAPK pathway inhibition (Fig. 3).…”
Section: Braf Mutation Status Is Predictive Of Changes In the Proteinsupporting
confidence: 87%
“…Targeting B-Raf(V600E) reduces tumor lung entrapment by decreasing the secretion of tumor IL-8 and interrupting ICAM-1-␤ 2 integrin binding of tumor cells to the endothelium, which is mediated by neutrophils in circulation (16). Furthermore, the roles of B-Raf(V600E) in inducing MMP-1 secretion and activating adjacent fibroblasts in the tumor microenvironment have been demonstrated (51). In this study, we showed a mechanistic link between B-Raf(V600E), TF expression, thrombin production, and endothelial junction breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…BRAF pathway activation has been linked to increased expression of Twist1 and Zeb1 resulting in greater melanoma invasion [24]. In addition, BRAF mutation potentiates the NFκB pathway; NFκB promotes MMP expression, increasing migratory capacity, and induces expression of Snail, a known driver of metastasis [12,37]. Further downstream, BRAF mutation has been linked to compensatory increases in ERK and subsequent overexpression of MITF [38].…”
Section: Signaling Pathways Inducing Emt In Melanomamentioning
confidence: 99%
“…Further downstream, BRAF mutation has been linked to compensatory increases in ERK and subsequent overexpression of MITF [38]. In addition, melanocytes expressing BRAF V600E synthesize more MMP-1 and promote greater stromal fibroblast activation than wild-type BRAF melanoma thus promoting greater cell motility [37]. …”
Section: Signaling Pathways Inducing Emt In Melanomamentioning
confidence: 99%